2011
DOI: 10.1155/2011/912720
|View full text |Cite
|
Sign up to set email alerts
|

The Default Mode Network and Altered Consciousness in Epilepsy

Abstract: Abstract. The default mode network has been hypothesized based on the observation that specific regions of the brain are consistently activated during the resting state and deactivated during engagement with task. The primary nodes of this network, which typically include the precuneus/posterior cingulate, the medial frontal and lateral parietal cortices, are thought to be involved in introspective and social cognitive functions. Interestingly, this same network has been shown to be selectively impaired during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 66 publications
(103 reference statements)
4
92
0
2
Order By: Relevance
“…These results confirm a previous report of normalized RSFC of right hippocampus with ECT, though our methodological approaches differed (33). PCC and precuneus share direct anatomical connections with the hippocampus (34; 35), and together with medial PFC form the default mode RSN widely implicated in self-referential processing and depression (3638), and aspects of epilepsy (39). The hippocampus is also a key structure in the pathophysiology of seizure disorders (e.g., temporal lobe epilepsy) (40), perhaps indicating that this structure is vulnerable to (and may even help to propagate) seizure activity elicited during ECT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm a previous report of normalized RSFC of right hippocampus with ECT, though our methodological approaches differed (33). PCC and precuneus share direct anatomical connections with the hippocampus (34; 35), and together with medial PFC form the default mode RSN widely implicated in self-referential processing and depression (3638), and aspects of epilepsy (39). The hippocampus is also a key structure in the pathophysiology of seizure disorders (e.g., temporal lobe epilepsy) (40), perhaps indicating that this structure is vulnerable to (and may even help to propagate) seizure activity elicited during ECT.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy research suggests these regions are impacted during seizures (63). Notably, the cerebellum exhibits increased activity during post-ictal phase (i.e., a period of altered consciousness following a seizure) (39; 63), and may influence thalamocortical circuits to aid in seizure termination and suppression (39; 64). In our study, functional plasticity in the cerebellum and other regions exhibiting ΔECT effects in the absence of ΔMD effects may reflect nonspecific physiological effects of seizure-related processes.…”
Section: Parsing the Lasting Effects Of Seizure Therapymentioning
confidence: 99%
“…The default mode network has been hypothesized on the basis of the observation that specific regions of the brain are consistently activated during the resting state but deactivated when engaged with tasks (Danielson et al, 2011). This network is assumed to be selectively impaired during epileptic seizures associated with loss of consciousness, such as absence seizures.…”
Section: Source Strength Of Hfos and Clinical Correlationmentioning
confidence: 99%
“…Also, Takaya et al (2006) demonstrated prefrontal hypometabolism and hypo-function in patients with intractable MTLE who also showed cognitive impairment (Takaya et al, 2006). Reduced connectivity in the DMN in MTLE patients has been also correlated with loss of consciousness (Cauda et al, 2009, Danielson et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Although most RSNs connectivity studies in MTLE patients aimed to understand the cognitive deficiencies often reported in those patients (Cataldi et al, 2013), some of these networks have been shown to be highly affected during rest (Maneshi et al, 2014, seizures (Danielson et al, 2011) and inter-ictal spikes (Laufs et al, 2007b, Fahoum et al, 2012.…”
Section: Seizures and Spikes)mentioning
confidence: 99%